Analysis of women’s treatment in Spanish press. Women’s International Day - Gómez y Patiño, María (Estudios sobre el Mensaje Periodístico, 2011)
This work describes the analysis and evaluation of the journalistic treatment that mass media devote to Women’s International Day. This study focuses on six points. The results of all of them, this is the conjunction of qualitative and qualitative characteristics together with the effects produced by selection of the journalistic agenda or the effects produced by publicity or humour allow the know the position of women within the everyday national written press. The conclusions and their interpretations is the space for discussion: if the place occupied by women is the deserved space or if on the contrary this place should be occupied by women every single day in the year either as an emergent item or one regular and stable one.